Extracorporeal Shock Wave Lithotripsy in Management of Urolithiasis - Hamal, Bhairab Kumar; Bhandari, Bharat Bahadur; Thapa, Narayan (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Since 1980, when Chaussy in West Germany first demonstrated the efficacy of Dornier prototype lithotripsy HM1, extra corporeal shock wave lithotripsy has become a convenient, noninvasive, outpatient procedure used to fragment urinary stones. It is a standard internationally accepted first line preferred option for the management of renal stone less than 2.5 cm size. Methods: A cross sectional study was conducted in the department of surgery of Shree Birendra Hospital on outpatient department basis during the period of March 2002 to February 2012. All consecutive patients presenting with renal and upper ureteric stones detected either on X-ray or ultrasound of the Kidney- Ureter-Bladder who were treated with extra corporeal shock wave lithotripsy. Descriptive analysis included age, sex, stone location, need of total session, use of double J stent and complications. Results: Total 710 diagnosed cases of urolithiasis were taken for the study. The youngest age was 16 years and oldest 69 years of age. Overall stone clearance rate was 73.52%. The stone free rate for upper, middle, and lower calyx were 85.94%, 90.20% and 50.52% respectively. Conclusions: Extracorporeal shock wave lithotripsy was successful in the management of the stones smaller than 2.5 cm in all caliceal locations and minimal morbidity.Plain Language Summary ESWL with new generation Lithotripter was safe and effective in adult out patients with urolithiasis less than 2.5 cm in functioning kidney without distal obstruction or urine infection. Stone clearance was 70%. DJ stenting was done in stone larger than 2 cm. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13007 Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):4-7